The Correlation between Fiscal Policy and Economic Growth - Laura Obreja Brasoveanu; Iulian Brasoveanu (Theoretical and Applied Economics, 2008)
The analysis of the correlation between fiscal policy and economic growth represents an important and very debated topic in the theoretical and empirical literature. In this study we test the correlation between fiscal policy and economic growth in Romania, for the period 1990-2007. The correlation pattern between the real growth rate of the GDP and the categories of budgetary revenues reveals a link of negative causality between the economic growth and fiscal revenues.